Angiogenic effects of borate glass microfibers in a rodent model. Issue 12 (26th February 2014) - Lin, Yinan; Brown, Roger F.; Jung, Steven B.; Day, Delbert E.
Abstract The primary objective of this research was to evaluate the use of bioactive borate‐based glass microfibers for angiogenesis in soft tissue repair applications. The effect of these fibers on growth of capillaries and small blood vessels was compared to that of 45S5 silica glass microfibers and sham implant controls. Compressed mats of three types of glass microfibers were implanted subcutaneously in rats and tissues surrounding the implant sites histologically evaluated 2–4 weeks post surgery. Bioactive borate glass 13–93B3 supplemented with 0.4 wt % copper promoted extensive angiogenesis as compared to silica glass microfibers and sham control tissues. The angiogenic responses suggest the copper‐containing 13–93B3 microfibers may be effective for treating chronic soft tissue wounds. A second objective was to assess the possible systemic cytotoxicity of dissolved borate ions and other materials released from implanted borate glass microfibers. Cytotoxicity was assessed via histological evaluation of kidney tissue collected from animals 4 weeks after subcutaneously implanting high amounts of the borate glass microfibers. The evaluation of the kidney tissue from these animals showed no evidence of chronic histopathological changes in the kidney. The overall results indicate the borate 2glass microfibers are safe and effective for soft tissue applications. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 102A: 4491–4499, 2014.